Synthesis, characterization, and investigation of photochemical and in vitro properties of novel Zn(II) phthalocyanine - Yildiz, Yasemin Baygu; Kabay, Nilgun; Yildiz, Burak; Omeroglu, Ipek; Durmuş, Mahmut; Karagur, E. Riza; Akca, Hakan (Tubitak Scientific & Technological Research Council Turkey, 2024)
A new nonperipheral zinc(II) phthalocyanine bearing octa carboxylic acid ethyl ester derivative substituted triazole attached propylmercaptothiobenzylmercapto derivative was synthesized via the tetramerization reaction of phthalonitrile. The photochemical in vitro photodynamic activity of zinc(II) phthalocyanine (ZnPc-I), such as human nonsmall cell lung carcinoma cell lines, was investigated in this study. The singlet oxygen generation property of novel zinc(II) phthalocyanine (ZnPc-I) was also examined due to the significantly high singlet oxygen quantum yield of ZnPc-I (FD = 0.66). The antiproliferative effects of ZnPc-I were also investigated on the A549 and H1299 cell lines, and the results demonstrated that ZnPc-I had a strong antiproliferative effect on both cell lines.
Keywords: Photodynamic therapy (PDT); singlet oxygen; in vitro investigation; click reaction; zinc phthalocyanine